2019
DOI: 10.1142/s021987621940005x
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Mass Transfer in an Unsteady Second Grade Nanofluid with Viscous Heating Dissipation

Abstract: This study presents the boundary layer flow of a second grade fluid in a rotating reference frame. The model equations are solved numerically using the bivariate spectral quasi-linearization method to obtain the fluid properties. We investigate the effects of measurable quantities such as the rate of rotation, thermal diffusivity, energy dissipation, viscoelastic parameter and other material properties of the fluid on the flow. The results show that slow rotation leads to a quick decline in the thicknesses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The axial and normal components velocity, pressure distribution, and temperature in the filter chamber were obtained using the numerical scheme described in Equation (24). Unless otherwise stated in the figures or discussion in Section 4, we used the following parameter values to compute the numerical solutions: .…”
Section: Methods Of Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The axial and normal components velocity, pressure distribution, and temperature in the filter chamber were obtained using the numerical scheme described in Equation (24). Unless otherwise stated in the figures or discussion in Section 4, we used the following parameter values to compute the numerical solutions: .…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…Additional studies in which spectral-based linearization methods have been applied to understand the dynamics of heat and mass transfer problems include, but are not limited to. [24][25][26][27][28] In each of these studies, the technique was reported to be accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this enhancement, the fluid exhibits unique properties, which facilitate heat and mass transfer. Since the pioneering study of the nanofluid model by Choi and Eastman, 1 an increasing number of studies have been carried out on this class of the fluid, such as Abbas et al, 2 Goqo et al, 3 Oloniiju et al, 4 and Oyelakin et al 5 …”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering study of the nanofluid model by Choi and Eastman, 1 an increasing number of studies have been carried out on this class of the fluid, such as Abbas et al, 2 Goqo et al, 3 Oloniiju et al, 4 and Oyelakin et al 5 Hybrid nanofluids are fluids that contain two or more nanoparticles added to pure fluids. They are mostly used in heat transfer apparatuses such as air conditioning systems, exchanger, heat sink, and plates.…”
Section: Introductionmentioning
confidence: 99%
“…The single-domain BSQLM was introduced by Motsa et al 39 and used in solving nonlinear evolution partial differential equations (PDEs). Subsequently, the method has been employed by several researchers [40][41][42][43][44] in solving boundary layer flow problems. The singledomain BSQLM method uses quasilinearization technique, 45 the Chebyshev spectral collocation method, as well as the bivariate Lagrange interpolation polynomial with Chebyshev-Gauss-Lobatto grid points.…”
Section: Introductionmentioning
confidence: 99%